Dietary Oligosaccharides Attenuate Stress-Induced Disruptions in Immune Reactivity and Microbial B-Vitamin Metabolism - Allen, Jacob M.; Jaggers, Robert M.; Solden, Lindsey M.; Loman, Brett R.; Davies, Ronald H.; Mackos, Amy R.; Ladaika, Christopher A.; Berg, Brian M.; Chichlowski, Maciej; Bailey, Michael T. (Frontiers in Immunology, 2019)
Background Exposure to stressful stimuli dysregulates inflammatory processes and alters the gut microbiota. Prebiotics, including long-chain fermentable fibers and milk oligosaccharides, have the potential to limit inflammation through modulation of the gut microbiota. To determine whether prebiotics attenuate stress-induced inflammation and microbiota perturbations, mice were fed either a control diet or a diet supplemented with galactooligosaccharides, polydextrose and sialyllactose (GOS+PDX+SL) or sialyllactose (SL) for 2 weeks prior to and during a 6-day exposure to a social disruption stressor. Spleens were collected for immunoreactivity assays. Colon contents were examined for stressor- and diet- induced changes in the gut microbiome and metabolome through 16S rRNA gene sequencing, shotgun metagenomic sequencing and UPLC-MS/MS. Results Stress increased circulating IL-6 and enhanced splenocyte immunoreactivity to an ex vivo LPS challenge. Diets containing GOS+PDX+SL or SL alone attenuated these responses. Stress exposure resulted in large changes to the gut metabolome, including robust shifts in amino acids, peptides, nucleotides/nucleosides, tryptophan metabolites, and B vitamins. Multiple B vitamins were inversely associated with IL-6 and were augmented in mice fed either GOS+PDX+SL or SL diets. Stressed mice exhibited distinct microbial communities with lower abundances of Lactobacillus spp. and higher abundances of Bacteroides spp. Diet supplementation with GOS+PDX+SL, but not SL alone, orthogonally altered the microbiome and enhanced the growth of Bifidobacterium spp. Metagenome-assembled genomes (MAGs) from mice fed the GOS+PDX+SL diet unveiled genes in a Bifidobacterium MAG for de novo B vitamin synthesis. B vitamers directly attenuated the stressor-induced exacerbation of cytokine production in LPS-stimulated splenocytes. Conclusions Overall, these data indicate that colonic metabolites, including B vitamins, are responsive to psychosocial stress. Dietary prebiotics reestablish colonic B vitamins and limit stress-induced inflammation.